Genetic characterization of Neisseria meningitidis isolates recovered from patients with invasive meningococcal disease in Lithuania - Slavinska, Anželika; Kowalczyk, Magdalena; Kirkliauskienė, Agnė; Vizuje, Greta; Siedlecki, Paweł; Bikulčienė, Joana; Tamošiūnienė, Kristina; Petrutienė, Aurelija; Kuisiene, Nomeda (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionNeisseria meningitidis is a gram-negative bacterium responsible for life-threatening invasive infections known as invasive meningococcal disease and is associated with high fatality rates and serious lifelong disabilities among survivors.MethodsThis study aimed to characterize N. meningitidis isolates cultured from blood and cerebrospinal fluid collected between 2009 and 2021 in Lithuania, assess their genomic relationships with European strains, and evaluate the possibility of using a cost-effective method for strain characterization, thus improving the national molecular surveillance of invasive meningococcal disease. In total, 321 N. meningitidis isolates were collected and analyzed using multilocus restriction typing (MLRT). Amplification of the penA gene and restriction fragment length polymorphism analysis were performed to identify the modified penA genes. Based on the MLRT genotyping results, we selected 10 strains for additional analysis using whole-genome sequencing. The sequenced genomes were incorporated into a dataset of publicly available N. meningitidis genomes to evaluate genomic diversity and establish phylogenetic relationships within the Lithuanian and European circulating strains.ResultsWe identified 83 different strains using MLRT genotyping. Genomic diversity of N. meningitidis genomes analysed revealed 21 different sequence types (STs) circulating in Lithuania. Among these, ST34 was the most prevalent. Notably, three isolates displayed unique combinations of seven housekeeping genes and were identified as novel STs: ST16969, ST16901, and ST16959. The analyzed strains were found to possess virulence factors not commonly found in N. meningitidis. Six distinct penA profiles were identified, each with different frequencies. In the present study, we also identified N. meningitidis strains with new penA, NEIS0123, NEIS1320, NEIS1525, NEIS1600, and NEIS1753 loci variants. In our study, using the cgMLST scheme, Minimum Spanning Tree (MST) analysis did not identify significant geographic relationships between Lithuanian N. meningitidis isolates and strains from Europe.DiscussionDiscussion: To our knowledge, this is the first study to employ whole genome sequencing (WGS) method for a comprehensive genetic characterization of invasive N. meningitidis isolates from Lithuania. This approach provides a more detailed and precise analysis of genomic relationships and diversity compared to prior studies relying on traditional molecular typing methods and antigen analysis.